2020
DOI: 10.2478/amb-2020-0039
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Expression of DNA Methylation Related Genes in Leukocytes of Persons with Alcohol and Drug Dependence

Abstract: Background and objectives. Though numerous studies have shown that the dysregulation of the epigenetic control is involved in disease manifestation, limited data is available on the transcriptional activity of DNA methylation related genes in alcohol and drug addiction. With regard to this, in this study we analyzed the expression levels of genes involved in DNA methylation, including DNMT1, DNMT3a, MeCP2, MBD1, MBD2, MBD3 and MBD4, in blood samples of alcohol and drug dependent persons in comparison to health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
(44 reference statements)
1
2
0
Order By: Relevance
“…While MeCP2 does not directly measure DNA methylation, its key role in the methylation process suggests alterations in global methylation patterns in the liver due to ethanol. This lines up with other areas also showing altered MeCP2 expression after ethanol exposure and changes to this regulation after treatment for AUD (Aşçibaşi et al, 2023;Cui et al, 2020;Krasteva et al, 2020). The changes in Mecp2 expression raise questions about the longterm alterations of global methylation patterns and how these might play a role in inheritance.…”
Section: Methylation Changes and Intergenerational Inheritancesupporting
confidence: 64%
See 2 more Smart Citations
“…While MeCP2 does not directly measure DNA methylation, its key role in the methylation process suggests alterations in global methylation patterns in the liver due to ethanol. This lines up with other areas also showing altered MeCP2 expression after ethanol exposure and changes to this regulation after treatment for AUD (Aşçibaşi et al, 2023;Cui et al, 2020;Krasteva et al, 2020). The changes in Mecp2 expression raise questions about the longterm alterations of global methylation patterns and how these might play a role in inheritance.…”
Section: Methylation Changes and Intergenerational Inheritancesupporting
confidence: 64%
“…Studies which examine specific genes in individuals have seen an increase in DNA methylation and a reduction in gene expression of Period Circadian Regulator 2 (PER2) and Proopiomelanocortin (POMC) in heavy drinkers which were predictors of alcohol craving (Gangisetty et al, 2019;Muschler et al, 2010). Assessment of DNMTs show lowered DNMT-3b mRNA expression is associated with an increase of genomic DNA methylation in patients with alcoholism (Bönsch et al, 2006) and another study of DNMTs and methyl-CpG-binding domain proteins in the blood of individuals with AUD also show a downregulation of methyl-CpG binding domain protein 1 (MBD1) and methyl-CpG-binding protein 2 (MECP2/Mecp2) in the alcohol-dependent group (Krasteva et al, 2020). Interestingly, these differences in methylation seem to be related to patterns of consumptions with one study finding significantly lower DNA methylation levels in the leukocytes of heavy drinkers compared to non-drinkers and moderate drinkers when looked at cross-sectionally (Maeda et al, 2022) and another reported differential blood DNA methylation in certain CpG islands in former drinkers compared to current drinkers in a longitudinal study (Dugué et al, 2021).…”
Section: Human Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…These higher levels of DNA methylation were predictors of increased subjective alcohol craving and were associated with the amount of alcohol consumed during the Alcohol Taste Test [23,33]. Krasteva et al (2020) evaluated DNMT1, DNMT3a, and methyl-CpG-binding domain proteins in the blood of individuals with AUD, finding downregulation of MeCP2 and MBD1 in the alcohol-dependent group [34].…”
Section: Human Studiesmentioning
confidence: 99%